If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x=-7x+13
We simplify the equation to the form, which is simple to understand
6x=-7x+13
We move all terms containing x to the left and all other terms to the right.
+6x+7x=+13
We simplify left and right side of the equation.
+13x=+13
We divide both sides of the equation by 13 to get x.
x=1
| -.33(12x+3)+.125(48x+40)= | | 5x+30x-3=7(5x+5) | | 3x-10=14-3x | | n/3-6=8 | | 0.35*0.2= | | 14x^2-157=333+4x^2 | | y=2*0+24 | | n/3-6=6 | | 3t(t-5)+6t^3= | | 6x-3=16-43 | | .34x^2=32 | | 10=4-2h | | 0=x^3+10x^2-11 | | 4-2x=70 | | 210-7n=400 | | 9=7+2h | | 11-9x=91-37x | | 10=3h-5 | | 9x-2=8+7 | | 3(2a+5)= | | 8x-30=42 | | 7x^2-15=49+3x^2 | | -6x+25=-8x+3.7 | | 1/2+1/3= | | 4p-16-17p+3= | | hi=ih | | 11x+7=5x-3 | | t-7-4t= | | 187-3x=33x+23 | | 2.7=.3y | | 12-6c=24 | | 10=4+2c |